Tanggung Jawab Pengelola Gudang Mengenai Resi Gudang Terhadap Kelalaian yang Mengakibatkan Kerugian (Lex Jurnalica, 2013)
AbstractIn the framework of Indonesia's economic development, banking law society where many economic activities that ask serious attention in the development of which is legal in the bank or loan funds. In disbursement of funds or loan, the bank needs to make an assessment of the character, ability, capital, business prospects and security of the debtor. Guarantee that will be used in the distribution of funds is the warehouse receipt. Warehouse Receipt in this case is the issuing bank to its customers is the purpose of an effort to provide protection. This study aims to discover the rules of the law of protection of warehouse receipt allowing a warehouse receipt for Bank Guarantee. Method using a type of research study by the normative juridical nature of descriptive analytical research approach through legislation (statute approach) using the data collection tool library research to obtain secondary data sourced from primary legal materials and secondary legal materials with field data supported the form of interviews with informants which includes Futures Trading Regulatory Agency (Bappebti), Warehouse Management as a party entitled issuing warehouse receipts, and Banking Institutions such as Bank Rakyat Indonesia. Data analysis is a qualitative analysis. Under the Warehouse Receipt Law No.. 9 of 2006 on Warehouse Receipt last amended by Law No.. 9 of 2011 on the Amendment of Act No. 9 of 2006 on Warehouse Receipt is a proof of ownership of the goods stored in the warehouse and can be transferred, pledged as collateral for debt or used as document delivery. So that the warehouse receipt can be categorized as securities that can be pledged as collateral for debt.Keywords: legal protection, bank, warehouse receipt AbstrakDalam rangka pembangunan ekonomi Indonesia, bidang hukum perbankan dimana banyak masyarakat melakukan aktivitas perekonomian yang meminta perhatian serius dalam pembinaan hukumnya diantaranya ialah bank dalam menyalurkan dana atau kredit. Dalam penyaluran dana atau kredit maka bank perlu melakukan penilaian mengenai watak, kemampuan, modal, prospek usaha dan jaminan dari nasabah debitur. Jaminan yang akan digunakan dalam penyaluran dana adalah resi gudang. Resi Gudang dalam hal ini adalah yang mengeluarkan adalah bank kepada nasabahnya dengan tujuan untuk upaya memberikan perlindungan. Penelitian ini bertujuan untuk menemukan kaidah hukum perlindungan Resi Gudang sehingga memungkinkan Resi Gudang menjadi Jaminan bagi Bank. Metode penelitian menggunakan tipe penelitian yuridis normatif dengan sifat penelitian deskriftif analistis melalui pendekatan undang-undang (statute approach) dengan menggunakan alat pengumpul data studi kepustakaan untuk memperoleh data sekunder yang bersumber dari bahan hukum primer dan bahan hukum sekunder dengan didukung data lapangan berupa wawancara dengan informan yang meliputi Badan Pengawas Perdagangan Berjangka (Bappebti), Pengelola Gudang sebagai pihak yang berhak menerbitan Resi Gudang, dan Lembaga Perbankan seperti Bank Rakyat Indonesia. Analisis data adalah analisis kualitatif. Resi Gudang menurut Undang Undang No. 9 Tahun 2006 tentang Resi Gudang yang terakhir diubah dengan Undang Undang No. 9 Tahun 2011 tentang Perubahan Atas Undang Undang No. 9 Tahun 2006 tentang Resi Gudang adalah merupakan bukti kepemilikan atas barang yang disimpan di gudang dan dapat dialihkan, dijadikan jaminan utang atau digunakan sebagai dokumen penyerahan barang. Sehingga Resi Gudang dapat dikatagorikan sebagai Surat Berharga yang dapat dijadikan jaminan hutang. Kata kunci: perlindungan hukum, bank, resi gudang